Thimerosal: current sources of contact in Brazil - Vanessa Barreto Rocha; Maria Antonieta Rios Scherrer (Sociedade Brasileira de Dermatologia, 2014)
Thimerosal is an organic mercury derivative found in ophthalmic solutions and certain vaccines in Brazil. Although most studies suggest the prevalence of thimerosal sensitivity to be quite high, this condition does not currently have any clinical relevance. The present article surveyed 184 Brazilian products (151 topical medications and 33 vaccines) and found that thimerosal was only present in 3 ophthalmic solutions and 5 vaccines.